2021
DOI: 10.3390/agriculture11070639
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Some Fruit Quality Parameters during Development and Ripening of Three Apricot Cultivars and Effect of Harvest Maturity on Postharvest Maturation

Abstract: The objective of this study was to evaluate the fruit development, the quality at harvest and the shelf-life changes of three apricot cultivars—‘Spring Blush’, ‘Robada’, and ‘Kioto’—produced in the conditions of the Southwest Iberian Peninsula. Pomological characteristics and global quality (colour, firmness, total soluble solids, and total acidity) were weekly evaluated during fruit growth and ripening. Apricots were harvested at commercial ripening, and six and three days before, were tested for each harvest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…As the storage period progresses, the score of treated banana samples moves from negative axis to positive axis of PC1 and from positive axis to negative axis with PC2 as the shelf-life period showed a diagonal PLOS ONE upward shift in the PC1-PC2 plane. The similar results were observed with three cultivars of apricot to enhance its shelf life [59,86].…”
Section: Principle Component Analysissupporting
confidence: 84%
“…As the storage period progresses, the score of treated banana samples moves from negative axis to positive axis of PC1 and from positive axis to negative axis with PC2 as the shelf-life period showed a diagonal PLOS ONE upward shift in the PC1-PC2 plane. The similar results were observed with three cultivars of apricot to enhance its shelf life [59,86].…”
Section: Principle Component Analysissupporting
confidence: 84%
“…Turkish varieties had higher stone dimensions than foreign varieties. Mratinic et al, (2011) reported that the stone weight of twenty Macedonia wild apricot ranged from 1.81 to 4.85 g. The stone length and width were previously reported by Velardo-Micharet, et al, (2021) as from 26.4 to 28.2 mm and between 21.6 and 23.4 mm from apricot cultivars, respectively. Our results were in a close relationship with previous studies and minor differences are due to varieties or high altitudes that are affected by climatic factors and fruit characters.…”
Section: Morphometric Traits Of Turkish and Foreign Varietiesmentioning
confidence: 88%
“…Studies on fruit height, width, thickness, and 100 kernel weight were previously reported to vary from 14.0 to 19.17 mm, from 9.99 to 10.20 mm, from 3.3 to 6.27 mm, and from 28.7 to 65.1 g, respectively (Gezer et al, 2003;Vursavuş and Özgüven, 2004). Velardo-Micharet, et al (2021) declared fruit height, diameter, and weight as varying from 46.6 to 53.9 mm, 48.4 to 57.5 mm, and 58.0 to 97.4 g, respectively. Another study was carried out in the Iğdır region on six apricot cultivars, fruit and stone weights were recorded as 27.88-52.9 g and 1.96-2.94 g, respectively (Muradoğlu et al, 2011).…”
Section: Morphometric Traits Of Turkish and Foreign Varietiesmentioning
confidence: 99%
See 1 more Smart Citation